Pressure Fluctuation Characteristics of the Short-Radius Elbow Pipe for FBR in the Postcritical Reynolds Regime - Tadashi SHIRAISHI; Hisato WATAKABE; Hiromi SAGO; hidemasa YAMANO (Journal of Fluid Science and Technology, 2009)
For the Japan Sodium-cooled Fast Reactor, an experimental study on the fluctuating pressure of the hot legs was carried out with tests using a 1/3-scale model. The total resistance coefficient is consistent with the published data, and our research has given some additional data up to the Reynolds number of 8.0x106. The flow pattern in the postcritical regime is independent of a Reynolds number. The statistical examination revealed that fluctuating pressures on the pipe wall depend on the mean velocity but not on the viscosity of the fluid. Negative spikes of pressure appeared for high velocity. Based on these experimental data it is concluded that, there are similarity laws for the scale of a model and the property of fluid, but not for the velocity in the pipe. Theoretical considerations also gave a discussion how to extrapolate the fluctuating pressure to the actual hot-leg conditions.